The girl who thought in pictures : the story of Dr. Temple Grandin - Mosca, Julia Finley (Mosca, Julia Finley. Amazing scientists., 2017)
Describes the life and accomplishments of the animal scientist and designer of cruelty-free livestock facilities, from her early life and autism diagnosis through her journey to become a livestock expert.